Approximation Degree of Bivariate Generalized λ-Bernstein - Kantorovich Type Operators. (26th August 2022) - Agrawal, Purshottam Narain; Baxhaku, Behar; Singh, Sompal
Abstract: In the present paper, we consider a tensor product of a generalized λ -Bernstein-Kantorovich type operators and discuss its approximation properties by means of the complete and partial moduli of continuity, Lipschitz class and the Peetre's K-functional. Further, we define the GBS (Generalized Boolean Sum) operators of the above bivariate operators and investigate the convergence rate of these operators for the B o ¨ gel continuous and B o ¨ gel differentiable functions by using the mixed modulus of smoothness. Finally, we illustrate the rate of convergence and its comparison for the bivariate λ -Bernstein-Kantorovich type operators and the associated GBS operators by means of graphs and tables for certain functions by using Matlab algorithms.